A Four‐Month Randomized, Double‐Blind Evaluation of the Efficacy of Botulinum Toxin Type A for the Treatment of Glabellar Lines in Women with Skin Types V and VI - GRIMES, PEARL E.; SHABAZZ, DWANA (Dermatologic surgery, 2009)
BACKGROUND Histologic differences (e.g., dermal thickness, collagen fibers) between Caucasian and other racial and ethnic groups may affect wrinkle formation and influence responses to treatment with botulinum toxin type A (BoNT‐A). OBJECTIVE To evaluate the degree and duration of efficacy of 20 and 30 U of BoNT‐A for the treatment of glabellar lines in African‐American women with skin types V and VI. MATERIALS & METHODS Women aged 18 to 65 with a glabellar rhytid score of 2 or more at maximum frown on an investigator‐rated 4‐point facial wrinkle scale (FWS; 0=none, 3=severe) were eligible for this study. Patients were randomly assigned to receive 20 U or 30 U of BoNT‐A in the glabellar region. Evaluations were conducted at baseline and days 30, 60, 90, and 120 postinjection. The investigator and patient graded the severity of wrinkles at maximum frown and repose on the same 4‐point FWS. BoNT‐A was administered at the assigned dose, divided between five equal intramuscular injections into the procerus muscle, each corrugator muscle, and a site above the midpupillary line on each side. RESULTS The percentage of responders at maximum frown did not differ significantly between the two groups. Although not statistically significant, the effect lasted somewhat longer in the subjects receiving the 30 U dose. No differences were evident between groups at repose through day 120. Adverse events were mild and transient and did not differ between the groups. CONCLUSION These results indicate that doses of 20 and 30 U of BoNT‐A demonstrate efficacy and safety in African‐American women with skin types V and VI.